A Study of the Optical Properties of CuBr Thin Film - AI-Dahan, Z.T.; Abdulrida, M.C.; AI-Ani, Z.T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper we have studied the optical properties of CuBr thin films. Different sample thicknesses have been prepared by using thermal evaporation technique with 14.4 runlsec as the average deposition rate and 1 00Â°C as the substrate temperature.